KOLABORASI ILMU NAGHOM DAN PEMBELAJARAN TENSES DENGAN MENGGUNAKAN TEKNIK “TEPUK KELEDAI CERDIK” DI MTS ALMAHFUDZ - Arif Widyantoro; Ali Mutafi (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This collaboration between naghom science and teaching English will provide its own teaching art that is unique and different from teaching and learning at Madrasah Tsanawiyah. The objectives of the research at MTs Almahfudz Peniron are; provide naghom lessons that are easy to memorize and practice for students; provide logical, easy, simple and fun English learning to students; provide collaboration in naghom learning and tenses learning in a way that is full of innovation and creation so that students will find it easy and fun to learn it. This type of research is qualitative. In collecting data it used interview technique, observation, and documentation. Based on the data obtained in this study, there are several lessons about nadhom science, learning English about tenses, and learning using “tepuk keledai cerdik” technique which is comprehensive and collaborative.